Economic structures 20 years into the euro - Agostino Consolo; Vanessa Gunnella; Gerrit Koester; Kyriacos Lambrias; Paloma López-García; Carolin Nerlich; Filippos Petroulakis; Lorena Saiz; Roberta Serafini (European Central Bank (ECB), 2019)
Well-functioning economic structures are key for resilient and prospering euro area economies. The global financial and sovereign debt crises exposed the limited resilience of the euro area's economic structures. Economic growth was masking underlying weaknesses in several euro area countries. With the inception of the crises, significant efforts have been undertaken by Member States individually and collectively to strengthen resilience of economic structures and the smooth functioning of the euro area. National fiscal policies were consolidated to keep the increase in government debt contained and structural reform momentum increased notably in the second decade, particularly in those countries most hit by the crisis. The strengthened national economic structures were supported by a reformed EU crisis and economic governance framework. However, overall economic structures in euro area countries are still not fully commensurate with the requirements of a monetary union. Moreover, remaining challenges, such as population ageing, low productivity and the implications of digitalisation, will need to be addressed to increase economic resilience and long-term growth.
Keywords: E31; E32; E60; E62; F10; J11; O43; 330; economic structures; euro area; resilience; growth